THE LEGAL STATUS OF UNCERTIFIED LAND IN INDONESIA: CHALLENGES AND PATHWAYS TO OWNERSHIP CERTIFICATION UNDER AGRARIAN LAW - Hadrian, Endang (Jurnal Pembaharuan Hukum, 2024)
Every individual has the right to private property, and these rights cannot be taken arbitrarily. Before the enactment of the Basic Agrarian Law (UUPA) in Indonesia, a dualism in agrarian regulations existed, leading to various forms of land tenure. One such form is "girik," a document associated with generational land ownership, often without an official land certificate. Girik land is typically inherited and lacks formal certification, creating potential legal complications. This research employs normative juridical methods, focusing on secondary data to examine the legal status of girik as land ownership evidence under Indonesian agrarian law. The study addresses two key questions: (1) What is the legal standing of girik as proof of land ownership under Indonesian agrarian law? and (2) How can the status of girik land be converted into a formal certificate of ownership? Findings reveal that the UUPA does not recognize girik as valid proof of ownership, as confirmed by Supreme Court Decision No. 34/K/Sip/1960. The research underscores the importance of formalizing girik land to prevent future legal disputes.